THE EFFECT OF EDUCATIONAL PUZZLE GAMES ON BALANCED NUTRITION KNOWLEDGE AND ATTITUDES AMONG JUNIOR HIGH SCHOOL STUDENTS AT SMP NEGERI 7 BUKITTINGGI IN 2025 : EDUCATIONAL PUZZLE GAMES - Rinaldi, Risak; Kasra, Kamal; Elda, Frima (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Adolescent nutrition is a complex public health issue, encompassing undernutrition, overnutrition, and micronutrient deficiencies such as anemia. Nutritional imbalances during adolescence affect physical growth, brain development, academic performance, and long-term productivity. Therefore, innovative, engaging, and age-appropriate educational approaches are necessary. One such effective method is the use of educational games such as puzzles, which present nutritional messages in an interactive and enjoyable way. This study aimed to analyze the effect of the Balanced Nutrition Puzzle Game on students’ knowledge and attitudes toward balanced nutrition. Methods: A quasi-experimental design with a pre-test and post-test control group was used. The sample consisted of 60 junior high school students selected through purposive sampling, with valid and reliable questionnaires used as instruments. Results: The results showed a significant increase in knowledge and attitude scores in the intervention group after the puzzle game was implemented (p < 0.05), whereas the control group showed no significant changes. Conclusion: These findings suggest that the Balanced Nutrition Puzzle Game is an effective educational medium for improving adolescent understanding and promoting positive attitudes toward healthy eating and lifestyle.